Measurement of 87Sr/86Sr in limestones after acid leaching and direct injection in a liquid chromatograph coupled to a multicollector ICP-MS. Issue 1 (20th December 2021) - Puente-Berdasco, B.; Rodríguez, J.; Ballesteros, D.; Painchault, A.; Nehme, C.; Mouralis, D.; Gil-Ibarguchi, J. I.; Martín-Izard, A.; Garcia Alonso, J. I.
Abstract : The 87 Sr/ 86 Sr isotope ratio in Normandy chalkstones has been measured by LC-MC-ICP-MS to help identify the quarries employed in the construction of medieval monuments. Abstract : A procedure for the measurement of 87 Sr/ 86 Sr in carbonates without off-line strontium separation was developed, validated and applied to Normandy chalkstones. The method is based on the injection of the dissolved/leached sample into a high-performance liquid chromatography (HPLC) system directly coupled to a multicollector inductively coupled plasma mass spectrometer (MC-ICP-MS). Matrix and spectral (Ca, Rb) interferences were removed by an on-line separation procedure based on cation exchange chromatography using 1 M nitric acid as an eluent in the presence of 3.8 mM 18-crown-6. The main polyatomic interferent was identified as NO2 Ca +, affecting mass 86 of strontium. Isotope ratios were calculated by multiple linear regression from the measured chromatographic peaks. The method was evaluated using a NIST 987 Sr isotope reference material and subsequently validated employing a JCp-1 coral reference material in comparison with the traditional off-line separation procedure. Finally, the method was applied to ten Normandy limestones (chalkstones) with results in agreement with the expected values based on geological, geochemical, and stratigraphic studies.